Использование отчетных таблиц "затраты-выпуск" для оптимизации структуры экономики - Карпец, Э.П. (Теорія оптимальних рішень, 2007)
In proposed article the principles of “input-output” tables usage for economy structure and dynamic forecasting are presented. The results obtained give the capability to assess tendencies of economic dynamics not only by means of such characteristics, as rates of traditional economic indicators’ growth, but also considering its structural shifts and the rate of econonomic balance.